2011
DOI: 10.1103/physreva.84.012104
|View full text |Cite
|
Sign up to set email alerts
|

Spin Hall effect on a noncommutative space

Abstract: We study the spin-orbital interaction and the spin Hall effect(SHE) of an electron moving on a noncommutative space under the influence of a vector potential A. On a noncommutative space we find that the commutator between the vector potential A and the electric potential V_1(r) of lattice induces a new term which can be treated as an effective electric field, and the spin-Hall conductivity obtains some correction. In addition, the spin current as well as spin-Hall conductivity have distinct values in differen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…In Ref. [15], SHE on noncommutative space was investigated, showing that on noncommutative space, these is a preferable direction for spin flow, and deformed accumulations of spin states on the edges of the sample will occur. Based on a semiclassical approach to noncommutative quantum mechanics, SHE has also been discussed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [15], SHE on noncommutative space was investigated, showing that on noncommutative space, these is a preferable direction for spin flow, and deformed accumulations of spin states on the edges of the sample will occur. Based on a semiclassical approach to noncommutative quantum mechanics, SHE has also been discussed in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies on the electromagnetic dynamics of the magnetic and electric dipole moments shown that both their global and local physical properties can be sensitive to non-trivial geometries [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. However, it is still difficult to observe them experimentally.…”
Section: Hua-wei Fanmentioning
confidence: 99%
“…At present days, the quantum Hall effect has been investigated in non-inertial systems [8][9][10][11], in the presence of topological defects [12,13], in Aharonov-Casher systems [14][15][16], anyons [17], graphene [18,19], superconducting arrays [20], noncommutative quantum mechanics [21][22][23][24] and in a background of the violation of the Lorentz symmetry [25]. In studies of the quantum Hall effect, the Landau quantization [26,27] is the simplest system that we can work with, then, with the purpose of extending to neutral particle systems, analogues of the Landau quantization have been proposed in recent years to neutral particles that possess permanent magnetic dipole moment [14], permanent electric dipole moment [28,29] and electric quadrupole moment [30].…”
Section: Introductionmentioning
confidence: 99%